2021
DOI: 10.1007/s11262-020-01811-y
|View full text |Cite
|
Sign up to set email alerts
|

Peste des petits ruminants virus non-structural C protein inhibits the induction of interferon-β by potentially interacting with MAVS and RIG-I

Abstract: Peste des petits ruminants virus (PPRV) causes an acute and highly contagious disease in domestic and wild small ruminants throughout the world, mainly by invoking immunosuppression in its natural hosts. It has been suggested that the non-structural C protein of PPRV helps in evading host responses but the molecular mechanisms by which it antagonizes the host responses have not been fully characterized. Here, we report the antagonistic effect of PPRV C protein on the expression of interferon-β (IFN-β) through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
3
8
0
Order By: Relevance
“…Mock- and PPRV-infected cells were used as negative and positive control, respectively. Our data showed that PPRV infection significantly suppressed alpha interferon (IFN-α) ( Fig 6A ) and gamma interferon (IFN-γ) ( Fig 6B ) expression, while stimulated expressionof tumor necrosis factor α (TNF-α) ( Fig 6C ), interleukin 4 (IL-4) ( Fig 6D ), and interleukin 10 (IL-10) ( Fig 6E ) as previously described [ 11 , 16 , 42 44 ]. Similar effects of EVs-PPRV or EVs-pcDNA3.1-H on the expression of these cytokines by the recipient cells compared to that of respective control was detected ( Fig 6A–6E ).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Mock- and PPRV-infected cells were used as negative and positive control, respectively. Our data showed that PPRV infection significantly suppressed alpha interferon (IFN-α) ( Fig 6A ) and gamma interferon (IFN-γ) ( Fig 6B ) expression, while stimulated expressionof tumor necrosis factor α (TNF-α) ( Fig 6C ), interleukin 4 (IL-4) ( Fig 6D ), and interleukin 10 (IL-10) ( Fig 6E ) as previously described [ 11 , 16 , 42 44 ]. Similar effects of EVs-PPRV or EVs-pcDNA3.1-H on the expression of these cytokines by the recipient cells compared to that of respective control was detected ( Fig 6A–6E ).…”
Section: Resultssupporting
confidence: 84%
“…Mock-and PPRV-infected cells were used as negative and positive control, respectively. Our data showed that PPRV infection significantly suppressed alpha interferon (IFN-α) (Fig 6A [11,16,[42][43][44]. Similar effects of EVs-PPRV or EVs-pcDNA3.1-H on the expression of these cytokines by the recipient cells compared to that of respective control was detected (Fig 6A -6E).…”
Section: Pprv Associate Evsregulate Slam Mediated Cytokines Expressio...supporting
confidence: 65%
“…PPRV C protein wasn’t able to bind MDA-5 and RIG-I, but PPRV lacking C protein expression lost the ability to block both MDA-5 and RIG-I mediated IFN induction [ 175 ]. A recent paper confirmed that C protein of PPRV blocks RIG-I or MAVS mediated IFN β reporter activation [ 176 ]. Interestingly, using C protein from different genera, in particular SeV, bPIV3, MeV, and NiV C proteins, Yamaguchi et al showed that all the C proteins bind to IKKα and inhibit IRF7 phosphorylation, and thus block toll-like receptor (TLR) 7- and TLR9-dependent IFN-α induction, which is a hallmark of activation of plasmacytoid dendritic cells ( Figure 2 ) [ 115 ].…”
Section: Role Of the P V And W Proteins In Ifn Antagonismmentioning
confidence: 85%
“…Although we did observe co-localization of PPRV-V with caMAVS in transfected cells, further studies will be required to fully understand the degradative interplay between PPRV-V and caMAVS. Interestingly, PPRV-C protein has recently been demonstrated to inhibit IFN-β induction by interacting with RIG-I and MAVS [44], which might indicate that both PPRV-V and PPRV-C are critical for counteracting the innate immune response. Since the results described in this study are based on the PPRV vaccine strain from lineage II, it would be interesting to follow up on this research to investigate commonalities and potential differences between the four circulating lineages [45] in their ability to counteract caMAVS.…”
Section: Discussionmentioning
confidence: 99%